2010
DOI: 10.1021/ie901001c
|View full text |Cite
|
Sign up to set email alerts
|

Investigation on the Spherical Crystallization Process of Cefotaxime Sodium

Abstract: In order to obtain satisfied spherical agglomerated product and overcome the incomplete removal of the impurity during the traditional spherical agglomerated process, a new strategy incorporating the spherical agglomeration technique and the drowning-out crystallization process, by which the impurities can be efficiently removed, was performed. A triangular phase diagram showing the phase equilibrium of ternary solvent mixtures used in the process of spherical crystallization was constructed and the real-time … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
41
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 37 publications
(45 citation statements)
references
References 18 publications
4
41
0
Order By: Relevance
“…The solubility of EES in different pure solvents was determined by using the gravimetric method [14][15][16][17]. The temperature was controlled by a thermostat bath (Julabo CF41, Germany) with uncertainty of ± 0.01 K. All samples were dried in a vacuum oven at 318.15 K until the total weight didn't change over time.…”
Section: Solubility Measurementmentioning
confidence: 99%
“…The solubility of EES in different pure solvents was determined by using the gravimetric method [14][15][16][17]. The temperature was controlled by a thermostat bath (Julabo CF41, Germany) with uncertainty of ± 0.01 K. All samples were dried in a vacuum oven at 318.15 K until the total weight didn't change over time.…”
Section: Solubility Measurementmentioning
confidence: 99%
“…Modeling studies reported so far were devoted to the analysis of copolymer composition, 15,16 molecular weight distribution, 16 length of the blocks, 17 distribution of the number of blocks per chain 18 and to finer microstructure analysis and its evolution during the polymerization. 19,20 It has notably been shown that the Mayo − Lewis equation 34 may no longer be able to describe the composition of the copolymers formed instantaneously by each catalyst in CSP systems operating in a continuous stirred tank reactor (CSTR).…”
Section: Theoretical Modeling Of Cspmentioning
confidence: 99%
“…Katta and coworkers (30) noticed no change in the particle size of agglomerated benzoic acid with an increased volume of bridging liquid. However, it can be concluded from other studies that if the quantity of bridging liquid is too small, there is no significant agglomeration and when too much bridging liquid is used, the agglomerates become soft and pasty (18,28,31). Some authors emphasize the importance of the choice of bridging liquid and suggest how to determine the optimal one for spherical agglomeration.…”
Section: Spherical Agglomerationmentioning
confidence: 99%
“…Another important process parameter is the proportion of good solvent to poor solvent. Zhang and coworkers have recently reported that the mean particle size of cefotaxime sodium spherical agglomerates increased with an increase of the poor solvent chloroform content in the crystallization system, and at the same time the particle size distribution became narrower, which can be ascribed to higher supersaturation and more effective crystallization and agglomeration (31). In that study, the temperature and agitation speed had no notable impact on the agglomerated particle size, while in another study (34) higher temperature resulted in smaller particle size and increased density of agglomerated carbamazepine.…”
Section: Spherical Agglomerationmentioning
confidence: 99%